Applying the principles of Gestalt theory to teaching ethics - Hunt, Eugene H. (Journal of business ethics, 1991)
Teaching ethics poses a dilemma for professors of business. First, they have little or no formal training in ethics. Second, they have established ethical values that they may not want to impose upon their students. What is needed is a well-recognized, yet non-sectarian model to facilitate the clarification of ethical questions. Gestalt theory offers such a framework. Four Gestalt principles facilitate ethical clarification and another four Gestalt principles anesthetize ethical clarification. This article examines each principle, illustrates that principle through current business examples, and offers exercises for developing each principle.